Creating Robust Antimicrobial Materials with Sticky Tyrocidines - Wilma van Rensburg; Marina Rautenbach (MDPI AG, 2022)
Modified antimicrobial and antifouling materials and surfaces can be used to limit the propagation of microorganisms on various surfaces and minimise the occurrence of infection, transfer, and spoilage. Increased demand for 'green' solutions for material treatment has pushed the focus towards to naturally produced antimicrobials. Tyrocidines, cyclo-decapeptides naturally produced by a soil bacterium Brevibacillus parabrevis, have a broad spectrum of activity against Gram-positive and Gram-negative bacteria, filamentous fungi, and yeasts. Continual losses in tyrocidine production highlighted the possible association of peptides to surfaces. It was found in this study that tyrocidines readily associates with many materials, with a selectivity towards polysaccharide-type materials, such as cellulose. Peptide-treated cellulose was found to remain active after exposure to a broad pH range, various temperatures, salt solutions, water washes, and organic solvents, with the sterilising activity only affected by 1% SDS and 70% acetonitrile. Furthermore, a comparison to other antimicrobial peptides showed the association between tyrocidines and cellulose to be unique in terms of antimicrobial activity. The robust association between the tyrocidines and various materials holds great promise in applications focused on preventing surface contamination and creating self-sterilising materials.